Human cathepsin S, but not cathepsin L, degrades efficiently MHC class II-associated invariant chain in nonprofessional APCs - Jacek Bania; Evelina Gatti; Hugues Lelouard; Alexandre David; Francesco Cappello; Ekkehard Weber; Voahirana Camosseto; Philippe Pierre (2003)
MHC class II-restricted antigen presentation plays a central role in the immune response against exogenous antigens. The association of invariant (Ii) chain with MHC class II dimers is required for proper antigen presentation to CD4 + T cells by antigen-presenting cells. MHC class II complexes first traffic through the endocytic pathway to allow Ii chain degradation and antigenic peptide loading before their arrival at the cell surface. In recent years, a considerable effort has been directed toward the identification of proteases responsible for Ii chain degradation. Targeted gene deletion in mice has allowed a precise description of the cysteine proteases involved in the last step of Ii chain degradation. By using nonspecialized cellular models expressing MHC II molecules, we are now exploring the contribution of known cysteine proteases to human Ii chain processing. Surprisingly and contrary to the situation in mouse, cathepsin S was found to be the only human cysteine protease able to efficiently degrade the Ii-p10 fragment in epithelial cells. This selectivity has implications for thymic selection and indicates that differences between man and mice are probably more profound at this level than expected.